Fragility as Holiness and the Voice of Women in the Shadow of the Cross - Veronica, Thelma; Mawikere, Marde C. S.; Brek, Yohan (International Journal of Education, Information Technology, and Others, 2025)
This article explores the concept of fragility within Christian theology, specifically examining how the vulnerability of women in church ministry is encountered through the lens of holiness and the sacrificial work of Christ. Utilizing a vulnerability theology framework, the study analyzes how women live out their spiritual calling amid patriarchal church structures that often marginalize their roles and voices. By engaging with theological discourse on fragility, this article seeks to offer a renewed perspective on how women may embrace their vulnerability as a sacred element of their ministerial vocation. The research employs a qualitative methodology, incorporating literature review and analysis of church documents. The findings suggest that fragility is not merely a sign of weakness, but a transformative space in which women may participate in the broader redemptive work of God.